Case Report: Tubridge flow diverter for a ruptured fusiform aneurysm of the M1 segments of the middle cerebral artery - Wei, Sen; Wang, Jingjing; Guo, Xinbin; Guan, Sheng (Frontiers in Surgery, 2022)
We report a case of the middle cerebral artery (MCA) M1 segment ruptured fusiform aneurysm that was successfully treated using a domestic Tubridge flow diverter (TFD). A 40-year-old man was admitted to the hospital because of a headache and was diagnosed with subarachnoid hemorrhage. Cerebral angiography revealed a ruptured fusiform aneurysm in the M1 segment of the right MCA. TFD, combined with coil embolization, was used for perioperative treatment. No obvious complications were observed. Follow-up digital subtraction angiography 2 and 12 months after the surgery showed that the aneurysm was occluded, and the patient recovered well. This is the first known case of this treatment with this type of stent in such an aneurysm and demonstrates that TFD can be used to treat ruptured fusiform aneurysms in the M1 segment of the MCA.